THE EFFECT OF THE UTILIZATION OF VISUAL AND AUDIO MEDIA LEARNING STYLE ON THE RESULTS OF LEARNING PAI IN THE FIRST MIDDLE SCHOOL INTEGRATED ISLAM NURUL FADHILAH PERCUT SEI TUAN - Sit, Masganti; Dahlan, Zaini; Panjaitan, Siti Rohimah (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2021)
The purpose of this study was to determine: (1) differences in islamic religious education learning outcomes of students who were taught using audio-visual media with image media, (2) differences in islamic religious education learning outcomes of students with visual, auditory and kinesthetic learning styles, (3) differences in student learning outcomes with visual learning styles taught using audiovisual media and picture media in the experimental and control classes, (4) differences in student learning outcomes with auditory learning styles taught using audiovisual media and picture media in the experimental and control classes, (5) differences in student learning outcomes with kinesthetic learning styles taught using audiovisual media and picture media in the experimental and control classes, and (6) interaction between learning media and learning styles on learning outcomes of islamic religious education.Â  The research findings show: (1) there are differences in the learning outcomes of islamic religious education students who are taught using audio-visual media with image media that have been verified through statistical testing, (2) there are differences in student learning outcomes of islamic religious education with visual, auditory and kinesthetic learning styles, this is evident from statistical testing, (3) there are differences in student learning outcomes with visual learning styles taught using audiovisual media and image media, this is proven based on the results of statistical tests, (4) there are differences in student learning outcomes with auditory learning styles taught using audiovisual media and image media, this is proven based on the results of statistical testing, (5) there are differences in student learning outcomes with kinesthetic learning styles taught using audiovisual media and image media, this is proven through the results of statistical testing, (6) there is interaction of learning media and learning styles on learning outcomes of Islamic Religious Education subjects